Complementation of un-16 and the development of a selectable marker for transformation of Neurospora crassa - Kevin McCluskey; Sheera A Walker; Rachel L Yedlin; David Madole; Michael Plamann (Fungal Genetics Reports, 2007)
Although nearly sixty temperature-sensitive lesions have been mapped in Neurospora crassa, most of their functions have not been identified. These loci are called unknown (un). As part of an effort to identify the open reading frame associated with one of these, we undertook to walk to un-16 using the complementation of temperature-sensitivity as a selection. Cosmids complementing un-16 were identified and the un-16 gene was subcloned. DNA sequence analysis of un-16 revealed that it encodes the highly conserved S9 protein of the 40S ribosomal subunit. This gene has proven useful as a selectable marker and may provide a simple mechanism for the controlled alteration of protein synthesis in N. crassa.